Wellbore stability in geomechanics - Xu, Guangquan (2007)
Borehole instabilities can be encountered at any stage in the life of a well and they are the main cause of drilling difficulties, resulting in substantial expenditures, expensive loss of time, sometimes even in the loss of part of or even whole boreholes. The main aim of this research is to use new method and theory in geomechanics to conduct the stability analysis of wellbore.